Impact of the SARS-CoV-2 pandemic on access to contraception and pregnancy intentions: a national prospective cohort study of the UK population. Issue 1 (21st October 2021) - Balachandren, Neerujah; Barrett, Geraldine; Stephenson, Judith M; Yasmin, Ephia; Mavrelos, Dimitrios; Davies, Melanie; David, Anna; Hall, Jennifer Anne
Abstract : Objective: Evaluate the impact of the COVID-19 pandemic on access to contraception and pregnancy intentions. Design: Nationwide prospective cohort study. Setting: United Kingdom. Participants: Women in the UK who were pregnant between 24 May and 31 December 2020. Main outcome measures: Access to contraception and level of pregnancy intentions, using the London Measure of Unplanned Pregnancy (LMUP) in women whose last menstrual period was before or after 1 April 2020. While the official date of the first UK lockdown was 23 March, we used 1 April to ensure that those in the post-lockdown group would have faced restrictions in the month that they conceived. Results: A total of 9784 women enrolled in the cohort: 4114 (42.0%) conceived pre-lockdown and 5670 (58.0%) conceived post-lockdown. The proportion of women reporting difficulties accessing contraception was higher in those who conceived after lockdown (n=366, 6.5% vs n=25, 0.6%, p<0.001) and continued to rise from March to September 2020. After adjusting for confounders, women were nine times more likely to report difficulty accessing contraception after lockdown (adjusted odds ratio (aOR) 8.96, 95% CI 5.89 to 13.63, p<0.001). There is a significant difference in the levels of pregnancy planning, with higher proportions of unplanned (n=119, 2.1% vs n=55, 1.3%) and ambivalent pregnancies (n=1163, 20.5% vs n=663, 16.1%) and lower proportions of planned pregnancies (n=4388, 77.4% vs n=3396, 82.5%) in the post-lockdown group (p<0.001). After adjusting for confounders, women who conceived after lockdown were still significantly less likely to have a planned pregnancy (aOR 0.88, 95% CI 0.79 to 0.98, p=0.025). Conclusions: Access to contraception in the UK has become harder during the COVID-19 pandemic and the proportion of unplanned pregnancies has almost doubled.